ABOUT THE TRANSLATION OF THE STORY ABOUT „MIRZA HAMDAM’S THE SIPARI GHAMI” (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article deals with the translation history of the book “Mirza Hamdam“, its translation by Sirojiddin Mahtum Sidiki in 1915 and its publication in Persian and Turkish lithographs, the overall transformation process and the main idea presented in it.